Species-specific roles of SP1 in bovine and human embryonic genome activation and early embryonic development - Hao Jin; Lieying Xiao; Xiaolin He; Bingjie Hu; Yan Shi; Bo Xu; Xiaomei Tong; Shaohua Wang; Panpan Zhao; Lei Luo; Kun Zhang (Proceedings of the National Academy of Sciences, 2026)
Embryonic genome activation (EGA) marks the onset of the embryonic program and enables the transition toward the first lineage specification. However, the molecular features of EGA and the transcription factors (TFs) orchestrating this process remain unclear. Here, by performing single-cell RNA-seq on bovine embryos, we reveal that major EGA is asynchronously initiated among blastomeres at the 8-cell stage. Integrative analyses reveal distinct protein accumulation compared with transcriptional and translational activation during bovine EGA. Furthermore, we investigate the role of SP1, a TF activated at the minor EGA stage, with motifs enriched in accessible chromatin during the major EGA stage in bovine and human embryos. SP1 deficiency leads to morula arrest in bovine and impairs EGA in human embryos. Multiomics analysis demonstrates that SP1 promotes early lineage gene expression by modulating nearby chromatin states in bovine and directly targets key EGA genes in human embryos. Together, our study delineates the dynamics of bovine EGA and uncovers the conserved and species-specific roles of SP1 in regulating EGA and early development in mammals.